2017
DOI: 10.1080/01480545.2017.1289221
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induced mitochondrial injury and cytochrome c release in rat liver hepatocytes

Abstract: Methotrexate (MTX) is a folic acid antagonist that is widely used to treat a variety of diseases. One of the most serious side effects of MTX therapy is hepatotoxicity. The potential molecular cytotoxic mechanisms of MTX toward isolated rat hepatocytes were investigated using Accelerated Cytotoxicity Mechanism Screening (ACMS) techniques. A concentration and time dependent increase in cytotoxicity and reactive oxygen species (ROS) formation and a decrease in mitochondrial membrane potential (MMP) were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 44 publications
6
27
0
Order By: Relevance
“…A new study in Proceedings of the National Academy of Sciences USA indicates that two-thirds of the brain's energy is used to help neurons send signals and the remaining third is used for cell-health maintenance, most of this energy is attained from ATP molecules through mitochondrial oxidative phosphorylation. Thus, we conclude that the reduction in ATP production is due to the harmful effects of MTX on the mitochondria, this result was previously recorded by 66 who established that MTX treatment caused swelling in the mitochondria of rats and significantly decreased adenosine triphosphate (ATP).…”
Section: Discussionsupporting
confidence: 79%
“…A new study in Proceedings of the National Academy of Sciences USA indicates that two-thirds of the brain's energy is used to help neurons send signals and the remaining third is used for cell-health maintenance, most of this energy is attained from ATP molecules through mitochondrial oxidative phosphorylation. Thus, we conclude that the reduction in ATP production is due to the harmful effects of MTX on the mitochondria, this result was previously recorded by 66 who established that MTX treatment caused swelling in the mitochondria of rats and significantly decreased adenosine triphosphate (ATP).…”
Section: Discussionsupporting
confidence: 79%
“…Methotrexate is an anti‐metabolite that inhibits dihydrofolic acid reductase thereby inhibiting purine and thymotic acid synthesis . It is an immunosuppressive agent with anti‐inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
“…Methotrexate is an anti-metabolite that inhibits dihydrofolic acid reductase thereby inhibiting purine and thymotic acid synthesis. 30 It is an immunosuppressive agent with anti-inflammatory effects. One study looking at the benefit of adding methotrexate to UDCA found no differences in treatment failure between the methotrexate and placebo arm.…”
Section: Methotrexate Colchicine and Atorvastatinmentioning
confidence: 99%
“…1), and we therefore demonstrated that this interaction is broadly applicable to both transformed and primary tissues. Although MTX is widely believed to mediate its pharmacological activity through inhibition of folate-dependent biochemical pathways, either through the depletion of the intracellular pool of bioactive folates or through the direct inhibition of the various folate-dependent enzymes, some investigators have suggested folate-independent pharmacological effects of MTX mediated through inhibition of Janus kinase/signal transducers and activators of transcription signaling, induction of oxidative stress, and mitochondrial toxicity (Phillips et al, 2003;Thomas et al, 2015;Zimmerman et al, 2017;Al Maruf et al, 2018). Therefore, we evaluated whether supplementation with folinic acid would reverse the increased antiproliferative effects of MTX in NAMPT-deficient cells (Fig.…”
Section: Discussionmentioning
confidence: 99%